1991
DOI: 10.2527/1991.6951945x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal influences on uterine and conceptus development in the cow: I. Growth of tissues of the gravid uterus

Abstract: Objectives of this study were to evaluate maternal and fetal influences on development of gravid uterine tissues of cows. Brahman cows with Brahman or Charolais fetuses and Charolais cows with Brahman or Charolais fetuses were used. Cows were killed 232 +/- .5 or 271 +/- .7 d after mating. The gravid uterus of each cow was weighed and dissected into its component parts. Weights of the fetus, fetal membranes, cotyledons, caruncles, and uterus were recorded as were weights of the fetal liver, heart, kidneys, spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 5 publications
4
42
1
3
Order By: Relevance
“…The effect of foetal and maternal genotype on foetal growth has been most convincingly demonstrated in cattle by Ferrell (1991) Joubert and Hammond (1958) for birth weights for South Devon and Dexter cattle and their reciprocal crosses. In this regard, foetal growth capacity as influenced by sex and siregenotype may also influence the nutritional status of the pregnant cow during late gestation (Greenwood et al, 2002b), probably due to differences in foetal nutrient uptake, contributing to maternal nutrient requirements.…”
Section: Paritymentioning
confidence: 99%
“…The effect of foetal and maternal genotype on foetal growth has been most convincingly demonstrated in cattle by Ferrell (1991) Joubert and Hammond (1958) for birth weights for South Devon and Dexter cattle and their reciprocal crosses. In this regard, foetal growth capacity as influenced by sex and siregenotype may also influence the nutritional status of the pregnant cow during late gestation (Greenwood et al, 2002b), probably due to differences in foetal nutrient uptake, contributing to maternal nutrient requirements.…”
Section: Paritymentioning
confidence: 99%
“…The concept of maternal and placental constraint involves a physiological homeostatic mechanism that ensures maternal survival (Ferrell 1991a,b, Gluckman et al 1992, and is related to the control of nutrient supply to foetuses in late gestation (Gluckman et al 1992). We observed previously that high birth weights following in vitro embryo manipulations are associated with early conceptus growth restriction and aberrant placentation (Bertolini & Anderson 2002, Bertolini et al 2002b.…”
Section: Introductionmentioning
confidence: 99%
“…Winick and Noble 1966;Robinson 1969;Greenwood et al 2000). In cattle, fetal growth restriction to about half normal growth during the period 232-271 days of gestation resulted in a 7.8% increase in muscle DNA content, compared with a 99.5% increase during normal fetal growth (Ferrell 1991). In this regard, it has been demonstrated that the number of satellite cells , replication of satellite cell nuclei (Greenwood et al 1999b) and subsequent accumulation of muscle DNA (Robinson 1969;Beermann 1983;Greenwood et al 2000) can be reduced by prenatal and/or early postnatal growth retardation with potential longer-term consequences for growth, body composition and body size (Widdowson 1971;Greenwood et al 1998).…”
Section: Musclementioning
confidence: 99%